MATH SOLVE

4 months ago

Q:
# Consider this system of linear equations:22x − y = -23 (equation 1)11x + 12y = 1 (equation 2)

Accepted Solution

A:

To solve this problem you must apply the proccedure shown below:

1. You have the folllowing system of equations given in the problem above:

22x − y = -23 (equation 1)

11x + 12y = 1 (equation 2)

2. If you multiply the equation 2 by -2, and then sum the equation 1+equation 2, you obtain:

-25y=-25

y=1

3. Then, you must substitute y=1 into the equation 1, then you have:

x=-1

4. As you can see, when you solve it, the solutions are:

x=-1

y=1

1. You have the folllowing system of equations given in the problem above:

22x − y = -23 (equation 1)

11x + 12y = 1 (equation 2)

2. If you multiply the equation 2 by -2, and then sum the equation 1+equation 2, you obtain:

-25y=-25

y=1

3. Then, you must substitute y=1 into the equation 1, then you have:

x=-1

4. As you can see, when you solve it, the solutions are:

x=-1

y=1